Analytic solutions of a two-fluid hydrodynamic model - Barna, Imre Ferenc; Mátyás, László (Mathematical Modelling and Analysis, 2021)
We investigate a one dimensional flow described with the non-compressible coupled Euler and non-compressible Navier-Stokes equations in the Cartesian coordinate system. We couple the two fluids through the continuity equation where different void fractions can be considered. The well-known self-similar Ansatz was applied and analytic solutions were derived for both velocity and pressure field as well.